Anemia in patients with type 1 diabetes mellitus - Tatiana Yur'evna Kufelkina (Endocrinology Research Centre, 2010)
Aim. To study the prevalence and structure of anemia syndrome in patients with type 1 diabetes mellitus (DM1) in Tatarstan. Materials and methods. Population-based screening studies for decreased blood Hb level were carried out in the cities of Kazan, Nabereznye Chelny,Chistopol and in the Arsk district. A total of 567 DM1 patients were involved; medical histories of 846 patients (54% of those registered in Kazan)were analysed. All patients were examined to elucidate the causes behind the reduced Hb level.Results and conclusions. Two screening techniques revealed anemia in 27 and 34% of the patients compared with 20% in the general population. Itsfrequency was estimated at 13% in the Arsk district. Anemia occurred more frequently in women than in men. The blood Hb level was directly relatedto GFR and inversely related to the presence of chronic renal disease and DM1 duration. Anemia of chronic disease (ACD) and iron deficiency anemia(IDA) prevailed in the structure of anemia syndrome in DM1 patients. These conditions accounted for 85.5% of all cases of anemia). IDA predominatedin patients without clinical manifestations of DN and in those with DN and preserved renal function while ACD associated with DN and impairedrenal function. Almost every third case of anemia was a combination of ACD and IDA. Folic acid deficiency was unrelated to the renal function